Generalization of the local approach application to the assessment of transfer processes in heat power equipment - Suprun, T.T. (Karagandy University of the name of academician E.A. Buketov, 2025)
In order to develop measures to improve the thermal efficiency of working surfaces and the coolant supply system, it is necessary to examine and analyze the results of comprehensive studies of transfer processes under complex conditions of interaction of external (increased turbulence) and internal (separation) turbulent effects typical for heat power equipment. The aim of the work is to develop methods for assessing transfer processes in such equipment based on local control of thermophysical parameters in characteristic zones of the working environment. The object of the study is heat exchange surfaces of power, chemical and electronic equipment, as well as coolant supply systems. The research method is physical modeling of turbulent effects of various natures and processes of heat, momentum and mass transfer using hot-wire, electro-calorimetric methods, and heat and mass analogy methods. The article considers the generalization of the local approach application on examples of assessing the influence of increased turbulence, local closed separations and unsteady flows on transfer processes in the flow part of heat power equipment for various purposes. A local approach to the development of an effective coolant supply system for the technology of final drying of plant waste fragments is also considered. The use of a local approach, which allows recording thermophysical parameters in any characteristic zone of the working space, provides the ability to control the most thermally stressed areas. These results are the basis for developing measures to increase the thermal efficiency of working surfaces.
Keywords: local thermophysical parameters; local aerodynamic characteristics; heat exchange surfaces; coolant supply system